Drill-down dashboard for chairing of online master programs in engineering - Silva, Anabela Costa e (2021)
Online masters’ program chairs need up-to-date information to monitor efficiently and effectively all the courses in the program for which they are responsible. Learning Management Systems supporting the operation of the online programme collect vast amounts of data about the learning process. These systems are geared to support individual teachers and students, not program chairs. This article presents the process that led to the development of a Dashboards for program chairs, based upon an analysis of their regular supervision tasks, decision-making information needs, and available data in the learning management system, Moodle. The information presented via the dashboard is aggregated and contextualised for all students enrolled in the program, in all its courses, contributing to improve decision-making in program chairing. The dashboard prototype is presented as a concrete outcome of this process, which can be replicated to achieve more advanced and updated versions, hopefully contributing to better program chairing.